2013
DOI: 10.17221/6652-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Morphological pattern of the livers of different lines of broiler chickens during rearing

Abstract: ABSTRACT:The aim of this study was to analyse the microscopic and ultrastructural lesions of the livers of broiler chickens during fattening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…It also performs a wide range of metabolic activities required for homeostasis, nutrition, and immune defense [ 13 ]. Subclinical infections are a major problem in broiler breeding and also result in liver damage [ 14 ]. Several studies have shown that subclinical infections with Clostridium perfringens are one of the main causes of liver damage in broiler chickens [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It also performs a wide range of metabolic activities required for homeostasis, nutrition, and immune defense [ 13 ]. Subclinical infections are a major problem in broiler breeding and also result in liver damage [ 14 ]. Several studies have shown that subclinical infections with Clostridium perfringens are one of the main causes of liver damage in broiler chickens [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that subclinical infections with Clostridium perfringens are one of the main causes of liver damage in broiler chickens [ 15 , 16 ]. Histopathologically, massive proliferation of bile ductules, proliferation of connective tissue around the ductules, hepatocyte necrosis, and massive lymphocyte and heterophil infiltration are observed in liver tissue as a result of its damage [ 14 , 15 , 16 ]. Additionally, in liver tissue of fast-growing broiler chickens, a significant group of degenerative regressive lesions have also been found [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the kidneys, parenchymatous and adipose degeneration of the proximal convoluted tubules epithelium, smooth muscle hypertrophy in the media of arteries and proliferative glomerulopathy were observed. The hepatocytes demonstrated cloudy swelling, smooth muscle hypertrophy in the media of arteries and proliferation of bile ductules (Gesek et al 2010(Gesek et al , 2013. In the lungs, an increased number of cartilaginous nodules and bone spicules were observed.…”
Section: Resultsmentioning
confidence: 99%